Epidemiology of Fractures Sustained During Electric Scooter Accidents: A Retrospective Review of 563 Cases. (16th June 2021) - Shichman, Ittai; Shaked, Or; Factor, Shai; Elbaz, Etay; Khoury, Amal
Abstract : Background: The use of electric scooters (e-scooters) has dramatically increased as they become an attractive alternative for public transportation in busy metropolitan areas worldwide. Despite their benefits, e-scooters challenge the health-care system with poorly understood forms of injuries, mainly orthopaedic fractures. To our knowledge, this study is the first to investigate e-scooter-related orthopaedic fracture patterns, mechanisms of injury, and management. Methods: Data on 3, 331 e-scooter-related admissions were retrospectively collected between May 2017 and February 2020 in a level-I trauma center. These admissions were analyzed for demographic variables, orthopaedic fracture diagnosis (using the AO/OTA classification), associated injuries, and surgical treatment. Results: During the study period, a total of 716 fractures were diagnosed in 563 patients, with 46.4% of the patients requiring hospitalization. Of 492 upper-limb fractures, 89.2% occurred in a rider fall mechanism; and of 210 lower-limb fractures, 15.7% occurred in rider-vehicle collisions. Fifty-nine percent of long bone fractures were complex fragmentary and/or intra-articular fractures. Orthopaedic surgeons recommended that 225 fractures undergo surgical treatment. The most common upper-limb fracture was AO/OTA class 2R1A, with open reduction and internal fixation of the distal part of the radius being the most common upper-limb procedure (n = 58). The most common lower-limb fracture was AO/OTA class 41C, with open reduction and internal fixation of the proximal part of the tibia being the most common procedure (n = 28). A total of 22 patients (3.9%) required reoperation within 1 year. Conclusions: This investigation provides unique information on demographic characteristics, patterns, and treatment of orthopaedic fractures secondary to the high-energy mechanism of e-scooter injuries. These new in-depth data are important, first, for health-care system preparedness with regard to management and resource allocation to treat these challenging injuries and, second, for legislators promoting safety and injury prevention strategies.